2000
DOI: 10.1038/sj.ijo.0801159
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum leptin in patients with coronary artery disease: no association with the Trp64Arg polymorphism of the β3-adrenergic receptor

Abstract: BACKGROUND: Serum leptin is associated with the occurrence of cardiovascular risk factors but it is unknown whether leptin is also associated with cardiovascular disease. Another open question is whether the Trp64Arg polymorphism of the b b 3 -adrenergic receptor (b 3 -AR) is a determinant of circulating leptin. OBJECTIVES: We measured serum leptin concentrations in a large group of patients with angiographically assessed coronary artery disease (CAD) and investigated the relationship between the Trp64Arg poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
1
16
4
Order By: Relevance
“…These findings suggest that leptin causes coronary vasodilation at subphysiologic leptin concentrations, but the degree of coronary vasodilation induced by leptin may decrease at or above physiologic leptin concentrations, and this phenomenon may be associated with "leptin resistance" (21). These factors may contribute to the differences seen between epidemiologic studies (19,20) and ours. It is likely that leptin may be used orally as an anti-obesity agent in the near future.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…These findings suggest that leptin causes coronary vasodilation at subphysiologic leptin concentrations, but the degree of coronary vasodilation induced by leptin may decrease at or above physiologic leptin concentrations, and this phenomenon may be associated with "leptin resistance" (21). These factors may contribute to the differences seen between epidemiologic studies (19,20) and ours. It is likely that leptin may be used orally as an anti-obesity agent in the near future.…”
Section: Discussioncontrasting
confidence: 53%
“…In addition, it is possible that differences in leptin concentration may contribute to the differing responses of the coronary arteries. In the present study, the baseline leptin concentration was 3.6 ng/ml and did not differ from the values reported ( 5 ng/ml) in the above studies (19,20). Although we showed that leptin-induced coronary vasodilation is not associated with the baseline leptin concentration, the mean body mass index was 24.5 0.8 kg/m 2 , and severely obese patients were not included in the present study.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…This difference is probably due to the fact that BMI in carcinoma patients was significantly lower than in patients with heart disease. This observation is in line with a recent report of higher plasma leptin concentrations in patients with coronary heart disease compared to a control group [29]. On the other hand, in cancer patients, a tendency of lower leptin levels has been described [30].…”
Section: Discussionsupporting
confidence: 80%
“…revealed that leptin was an independent risk factor for acute myocardial infarction even after adjustment of several cardiovascular risk factors, such as high BMI, blood pressure and hyperinsulinaemia (15). Meanwhile, a later cross-sectional study also demonstrated that serum leptin was a significant determinant of CAD in addition to other established cardiovascular risk factors, such as smoking, age, gender, fasting insulin and BMI, and the capacity of leptin activating the sympathetic nervous system was considered as pivotal role for the significant association (28). Notably, discrepant results observed from these and subsequent studies mainly attributed to different study design, particularly the different treatment for various cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 97%